Porcine Reproductive and Respiratory Syndrome Virus Type 1.3 Lena Triggers Conventional Dendritic Cells 1 Activation and T Helper 1 Immune Response Without Infecting Dendritic Cells - Bordet, Elise; Blanc, Fany; Tiret, Mathieu; Crisci, Elisa; Bouguyon, Edwige; Renson, Patricia; Maisonnasse, Pauline; Bourge, Mickael; Leplat, Jean-Jacques; Giuffra, Elisabetta; Jouneau, Luc; Schwartz-Cornil, Isabelle; et al. (Frontiers in Immunology, 2018)
Porcine Reproductive and Respiratory Syndrome virus (PRRSV) is an arterivirus responsible for highly contagious infection and huge economic losses in pig industry. Two species, PRRSV-1 and PRRSV-2 are distinguished, PRRSV-1 being more prevalent in Europe. PRRSV-1 can further be divided in subtypes. PRRSV-1.3 such as Lena are more pathogenic than PRRSV-1.1 such as Lelystad or Flanders13. PRRSV-1.3 viruses trigger a higher Th1 response than PRRSV-1.1, although the role of the cellular immune response in PRRSV clearance remains ill defined. The pathogenicity as well as the T cell response inductions may be differentially impacted according to the capacity of the virus strain to infect and/or activate DCs. However, the interactions of PRRSV with in vivo-differentiated-DC subtypes such as conventional DC1 (cDC1), cDC2, and monocyte-derived DCs (moDC) have not been thoroughly investigated. Here, DC subpopulations from Lena in vivo infected pigs were analyzed for viral genome detection. This experiment demonstrates that cDC1, cDC2, and moDC are not infected in vivo by Lena. Analysis of DC cytokines production revealed that cDC1 are clearly activated in vivo by Lena. In vitro comparison of 3 Europeans strains revealed no infection of the cDC1 and cDC2 and no or little infection of moDC with Lena, whereas the two PRRSV-1.1 strains infect none of the 3 DC subtypes. In vitro investigation of T helper polarization and cytokines production demonstrate that Lena induces a higher Th1 polarization and IFNγ secretion than FL13 and LV. Altogether, this work suggests an activation of cDC1 by Lena associated with a Th1 immune response polarization.